Diet Elimination of The Breastfeeding Mother in Treating Allergies of Infants Ages 0-12 - Cathryne, Joice; Kartika, Lia (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: Breast Milk (BM) is the primary nutrient that must be given to babies. Complete breast milk nutrients help the babies' growth, development, and boost immunity. Some data found that breastfeeding triggers infant allergies. Objectives: To critically appraise the evidence of the effectiveness of the breastfeeding mother's elimination diet (ED) in treating allergies of infants ages 0-12. Methods: A literature search was conducted for publication during 2016 – 2021 using the following databases: EBSCO, Google Scholar, and Proquest with the search keywords of "Elimination Diet" AND "Allergies" AND "Breastfeeding". Eight primary articles were selected and included in the review. Results: The study revealed five themes, namely the effectiveness of the elimination diet, the variation of the elimination diet, the effects of the elimination diet, the breast milk benefit, and the support from the family and healthcare while doing the elimination diet. Conclusion: Having babies with allergies can put mothers in a dilemma situation. Fortunately, a mother can still breastfeed their babies without worrying about their babies' growth. Support from health workers and families is needed by breastfeeding mothers in doing the elimination diet consistently.